1999
DOI: 10.1006/dbio.1999.9298
|View full text |Cite
|
Sign up to set email alerts
|

Chamber-Specific Cardiac Expression of Tbx5 and Heart Defects in Holt–Oram Syndrome

Abstract: To further define the role of a T-box transcription factor, Tbx5, in cardiac development, we have examined its expression in the developing mouse and chick heart and correlated this pattern with cardiac defects caused by human TBX5 mutations in Holt-Oram syndrome. Early in the developing heart, Tbx5 is uniformly expressed throughout the entire cardiac crescent. Upon formation of the linear heart tube, Tbx5 is expressed in a graded fashion, stronger near the posterior end and weaker at the anterior end. As the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
332
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(364 citation statements)
references
References 37 publications
27
332
0
5
Order By: Relevance
“…These results are in line with the spatial expression of Tbx5 as it is highly expressed in the posterior part of the linear heart tube (later atria) and builds a gradient toward the anterior part of the heart tube (later ventricles; Bruneau et al, 1999). With the overexpression, we provide a high level of Tbx5, so that an atrial fate develops preferentially, while ventricular fates require lower doses of Tbx5.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are in line with the spatial expression of Tbx5 as it is highly expressed in the posterior part of the linear heart tube (later atria) and builds a gradient toward the anterior part of the heart tube (later ventricles; Bruneau et al, 1999). With the overexpression, we provide a high level of Tbx5, so that an atrial fate develops preferentially, while ventricular fates require lower doses of Tbx5.…”
Section: Discussionsupporting
confidence: 81%
“…The cardiac specific expression of Tbx5 in mice can first be detected at embryonic day (E) 7.5 in the cardiac crescent, the FHF (Bruneau et al, 1999;Liberatore et al, 2000). Later in development, Tbx5 is found in the posterior heart tube, in the forming left ventricle and in both atria (Chapman et al, 1996;Bruneau et al, 1999) and thus labels cells of the FHF lineage. As in mouse development, Tbx5 expression is designated to the FHF lineage in Xenopus laevis (Gessert and Kü hl, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tbx5, which is normally expressed at highest levels in the atria and left ventricle 32 , was expressed at comparable levels in the Bop -/-and wildtype heart (Fig. 5o,p), consistent with the conclusion that the single ventricle in the absence of Bop is, on a molecular basis, primarily a left ventricle.…”
Section: Bop -/-Mice Show Ventricular Hypoplasia and Expanded Extracesupporting
confidence: 82%
“…Lineage tracing experiments studying Isl1 (Cai et al, 2003), Fgf 10 (Kelly, 2005), and Tbx5 (Bruneau et al, 1999;Liberatore et al, 2000), 18 (Christoffels et al, 2006), and Shox2 (Blaschke et al, 2007) have demonstrated the contribution of the second heart field to the formation of the atrial myocardium which has a distinct molecular composition compared with the heart tube derived from the primary heart field (Cai et al, 2003;Kelly, 2005;Anderson et al, 2006).…”
Section: Primary Atrial Septum and Dorsal Atrial Wallmentioning
confidence: 99%